2021
DOI: 10.1038/s41598-021-85804-3
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting ideational fluency in a creativity task across multiple transcranial direct current stimulation montages

Abstract: Neuroimaging and transcranial direct current stimulation (tDCS) research has revealed that generating novel ideas is associated with both reductions and increases in prefrontal cortex (PFC) activity, and engagement of posterior occipital cortex, among other regions. However, there is substantial variability in the robustness of these tDCS‐induced effects due to heterogeneous sample sizes, different creativity measures, and methodological diversity in the application of tDCS across laboratories. To address thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
(55 reference statements)
1
12
0
Order By: Relevance
“…In recent years, research into the effects of NIBS and causal neural mechanisms underlying creative cognition is increasing rapidly. However, inconsistent findings in this research is also increasing, likely due to differences in experimental design, stimulation parameters, and creative measures (Chrysikou et al, 2021). For example, previous studies have shown that increasing excitability (via anodal tDCS) over the right inferior fronal gyrus (IFG) coupled with decreasing excitability (via cathodal tDCS) over the left IFG improved performance in a verbal divergent thinking task, and a deteriorative effect was observed with the reverse stimulation protocol (Hertenstein et al, 2019;Mayseless and Shamay-Tsoory, 2015).…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…In recent years, research into the effects of NIBS and causal neural mechanisms underlying creative cognition is increasing rapidly. However, inconsistent findings in this research is also increasing, likely due to differences in experimental design, stimulation parameters, and creative measures (Chrysikou et al, 2021). For example, previous studies have shown that increasing excitability (via anodal tDCS) over the right inferior fronal gyrus (IFG) coupled with decreasing excitability (via cathodal tDCS) over the left IFG improved performance in a verbal divergent thinking task, and a deteriorative effect was observed with the reverse stimulation protocol (Hertenstein et al, 2019;Mayseless and Shamay-Tsoory, 2015).…”
Section: Introductionmentioning
confidence: 64%
“…Kleinmintz et al, (2018b) employed repetitive transcranial magnetic stimulation (rTMS) protocol with continuous theta-burst stimulation to inhibit the neural activation of left IFG and revealed a significant effect of stimulation that enhances originality scores in AUT. Conversely, some studies failed to find inhibitory activation of the left prefrontal cortex increased the generation of uncommon responses, but it works for appropriateness and fuency of participants' responses (Chrysikou et al, 2013;Chrysikou et al, 2021;Kenett et al, 2021). Moreover, the DLPFC was the most commonly used stimulation site and appears to work well for all-purpose cognitive enhancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This line of research suggests that stimulation may be “unleashing” creativity, mainly by modulating the bilateral temporal and prefrontal cortices. Placing the cathode over left and the anode over right cortical areas, in accordance with the hemispheric balance hypothesis, led to several studies finding positive results ( Chrysikou et al, 2021 , Hertenstein et al, 2019 , Ivancovsky et al, 2019 , Lifshitz-Ben-Basat and Mashal, 2021 , Mayseless and Shamay-Tsoory, 2015 ). According to this hypothesis, a shift in interhemispheric balance resulting in a predominance of the right over the left hemisphere promotes creativity.…”
Section: Boosting Intelligence and Creativity And The Role Of Trainin...mentioning
confidence: 74%
“…Results from transcranial stimulation studies mainly indicate that anodal tDCS over left DLPFC may increase DT (Colombo et al, 2015;Zmigrod et al, 2015;Peña et al, 2021) and CT (Cerruti and Schlaug, 2009;Metuki et al, 2012;Zmigrod et al, 2015;Peña et al, 2021Peña et al, , 2019. However, in separate studies, cathodal tDCS over the left IFG also found an increase in DT (Mayseless and Shamay-Tsoory, 2015;Kleinmintz et al, 2018;Hertenstein et al, 2019;Ivancovsky et al, 2019;Khalil et al, 2020;Chrysikou et al, 2021;Kenett et al, 2021).…”
Section: Introductionmentioning
confidence: 98%